USING VISUALIZATION AND TEXT MINING TO IMPROVE QUALITATIVE ANALYSIS: A FEASIBILITY STUDY - Hernandes, Elis Cristina Montoro; LaPES - Laboratório de Pesquisa em Engenharia de Software UFSCar - Universidade Federal de São Carlos (2013)
Context: Qualitative analysis is a scientific way to deeply understand qualitative data and to aid in its analysis. However, qualitative analysis is a laborious, time-consuming and subjective process. Aim: The authors propose the use of visualization and text mining to improve the qualitative analysis process. The objective of this paper is to explain how the use of visualization can support the Coding in multiple documents simultaneously, which may allow codes standardization thus making the process more efficient. Method: The Insight tool is being developed to make the proposal feasible and a feasibility study was performed to verify if the proposal offers benefits to the process and improves its results. Results: The study shows that the subjects who applied the proposal got more standardized codes and were more efficient than the ones who applied the process manually. Conclusions: Although the study was conducted in a restrict context (small subject’s group and generic data), the results derived from the use of the proposal encourage proceeding with the project.